High‐Fat Diet–Induced Obesity Promotes Expansion of Bone Marrow Adipose Tissue and Impairs Skeletal Stem Cell Functions in Mice. (5th March 2018) - Tencerova, Michaela; Figeac, Florence; Ditzel, Nicholas; Taipaleenmäki, Hanna; Nielsen, Tina Kamilla; Kassem, Moustapha
ABSTRACT: Obesity represents a risk factor for development of insulin resistance and type 2 diabetes. In addition, it has been associated with increased adipocyte formation in the bone marrow (BM) along with increased risk for bone fragility fractures. However, little is known on the cellular mechanisms that link obesity, BM adiposity, and bone fragility. Thus, in an obesity intervention study in C57BL/6J mice fed with a high‐fat diet (HFD) for 12 weeks, we investigated the molecular and cellular phenotype of bone marrow adipose tissue (BMAT), BM progenitor cells, and BM microenvironment in comparison to peripheral adipose tissue (AT). HFD decreased trabecular bone mass by 29%, cortical thickness by 5%, and increased BM adiposity by 184%. In contrast to peripheral AT, BMAT did not exhibit pro‐inflammatory phenotype. BM progenitor cells isolated from HFD mice exhibited decreased mRNA levels of inflammatory genes ( Tnfα, IL1β, Lcn2 ) and did not manifest an insulin resistant phenotype evidenced by normal levels of pAKT after insulin stimulation as well as normal levels of insulin signaling genes. In addition, BM progenitor cells manifested enhanced adipocyte differentiation in HFD condition. Thus, our data demonstrate that BMAT expansion in response to HFD exerts a deleterious effect on the skeleton. Continuous recruitment of progenitor cells to adipogenesis leads to progenitor cell exhaustion, decreased recruitment to osteoblastic cells, and decreased bone formation. In addition, the absence of insulin resistance and inflammation in the BM suggest that BMAT buffers extra energy in the form of triglycerides and thus plays a role in whole‐body energy homeostasis. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.